A REVIEW OF QUERY OPTIMIZATION IN DISTRIBUTED OBJECT ORIENTED RELATIONAL DATABASE MANAGEMENT SYSTEM (International Journal of Engineering Sciences & Management Research, 2015)
Execution of Structured Query Language (SQL) queries in optimized way in the distributed database is a hitch that most of the database programmer faces since the inception of database technology. Query optimization in network is one of the hardest problems in the database area. The commercialization and success of database systems is primarily due to the development of complicated query optimization techniques. Database users post their queries in a declarative mode by by means of SQL or Object Query Language (OQL) and the Query Optimizer of the related database system find a best plan to execute the same. The optimizer determines the best indices to be used to execute a query and the order in which the operations of a query should be executed. To achieve this, the optimizer estimate alternative plans, and also estimate the cost of query plan by means of a cost model, and then selects the plan with lowest cost. There has been much research into this field. In this paper, we will review the difficulty of distributed query optimization; and will emphasis on the various components of the query optimizer required in distributed environment, i.e. cost model, search space and search strategy. A review of the existing work in this field is shown and future work is highlighted based on recent work that utilizes mobile agent technologies.